2017
DOI: 10.24271/garmian.147
|View full text |Cite
|
Sign up to set email alerts
|

Functional properties of cow milk proteins co-precipitate

Abstract: The ideal conditions for preparation of cow milk proteins co-precipitate were investigated. The optimum concentration of calcium chloride used to prepare milk proteins co-precipitate was 25mM.This concentration of calcium yielded 96.2% of milk proteins. The best pH values to prepare milk proteins co-precipitate were between (5.5-6-6.5), while the best heat treatments used were between 85-95°C for 20 min. Solubility of co-precipitate in comparison with sodium caseinate was studied. There were no significant dif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
5
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 18 publications
0
5
0
Order By: Relevance
“…Reduced protein losses in the whey at a particular coagulant concentration are collectively associated with electrostatic shielding, hydrophobic interactions, and cross‐linking of the adjacent anionic molecule via bridging between protein and calcium molecules (Deeth & Lewis, 2015). Siamand and Al‐Saadi (2017) also determined protein recovery during the preparation of co‐precipitates from cow skim milk at 85°C/20 min. It was concluded that protein recovery increased with an increase in CaCl 2 concentration up to a certain level and decreased after that.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Reduced protein losses in the whey at a particular coagulant concentration are collectively associated with electrostatic shielding, hydrophobic interactions, and cross‐linking of the adjacent anionic molecule via bridging between protein and calcium molecules (Deeth & Lewis, 2015). Siamand and Al‐Saadi (2017) also determined protein recovery during the preparation of co‐precipitates from cow skim milk at 85°C/20 min. It was concluded that protein recovery increased with an increase in CaCl 2 concentration up to a certain level and decreased after that.…”
Section: Resultsmentioning
confidence: 99%
“…Co‐precipitation was not observed at lower temperatures (50–55°C) due to the lower binding of calcium with casein and lack of whey protein denaturation. Siamand and Al‐Saadi (2017) successfully prepared cow milk co‐precipitates employing heating at 85–95°C.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Co-precipitates from cow, buffalo, sheep, goat, and camel milk have been studied for their functionality by researchers (Mann 1982;Al-Saadi and Deeth 2011;Simand and Al-Saadi 2017;AlGhsyar et al 2018). Recently, Gawande et al (2022) optimised a process for preparation of Buffalo milk protein co-precipitates (BMPC) with enhanced solubility by modifying the protocol of Mann (1982).…”
Section: Introductionmentioning
confidence: 99%
“…Co‐precipitates from cow, buffalo, sheep, goat, and camel milk have been studied for their functionality by researchers (Mann 1982; Al‐Saadi and Deeth 2011; Simand and Al‐Saadi 2017; AlGhsyar et al . 2018).…”
Section: Introductionmentioning
confidence: 99%